The Impact of MOCK UP Media on Concept Understanding in Science Materials for Class V at SDN 9 Aceh Utara - Iza Fitria; Sarah Fazilla; Fauziana Fauziana (PGMI IAIN Lhokseumawe, 2023)
The low understanding of the concept of fifth-grade students at SDN 9 Aceh Utara in science lesson theme 4 sub-theme 1 is due to the minimal use of instructional media in the learning process, so there is a need for learning media that can improve students’ understanding of concepts, one of which is Mock Up media. This study aims to determine the effect of Mockup media on conceptual understanding in science subjects for class V theme 4 sub-theme 1 at SDN 9 Aceh Utara. This type of research is a quantitative research with an experimental approach. The population in this study were all fifth-grade students at SDN 9 Aceh Utara, totaling 71 students. Sampling using Random Sampling. The research sample was students from two classes, namely 23 students from class V A as the experimental class and 23 students from class V B as the control class. The data collection technique in this study was in the form of a test of 20 questions in the form of a pretest and posttest, with data analysis using SPSS 23. Hypothesis testing using t-test. Based on the research results obtained tcount = 3.513 and ttable = 2.015. This means that tcount > ttable, namely 3.513 > 2.015 at a significance level of 0.05, meaning reject H0 and accept Ha. It can be concluded that there is an influence of Mock Up media on understanding concepts in grade V science subjects, theme 4, sub-theme 1 at SDN 9 Aceh Utara.